KEYS TO SUCCESSFUL IMPLEMENTATION OF FLEXIBLE WORKING SPACE AS A NEW NORMALITY IN PUBLIC ORGANIZATIONS - M. Syamsul Maarif; Anggraini Sukmawati; Ahmad Rifai (School of Business, IPB University (SB-IPB), 2021)
COVID-19 caused a health crisis that prompted the acceleration of implementing the new